2010
DOI: 10.1016/j.bbapap.2009.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations in PI3Kα: Structural basis for enzyme activation and drug design

Abstract: The PI3K pathway is a communication hub coordinating critical cell functions including cell survival, cell growth, proliferation, motility and metabolism. Because PI3Kα harbors recurrent somatic mutations resulting in gains of function in human cancers, it has emerged as an important drug target for many types of solid tumors. Various PI3K isoforms are also being evaluated as potential therapeutic targets for inflammation, heart disease, and hematologic malignancies. Structural biology is providing insights in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
0
12
0
4
Order By: Relevance
“…In all crystal structures described thus far, the activation loop is disordered and not able to be seen, suggesting that the loop is flexible or disordered. Gabelli et al (2010), in their p110␣ structures comparing unliganded enzyme with enzyme bound to wortmannin, noted that the loop containing amino acids 772 to 776 (within region 2) changes conformation. Their modeling studies suggested that this loop was in the binding site for PIP 2 and that this mode of binding correctly positioned the lipid for phosphoryl transfer from ATP.…”
Section: Discussionmentioning
confidence: 99%
“…In all crystal structures described thus far, the activation loop is disordered and not able to be seen, suggesting that the loop is flexible or disordered. Gabelli et al (2010), in their p110␣ structures comparing unliganded enzyme with enzyme bound to wortmannin, noted that the loop containing amino acids 772 to 776 (within region 2) changes conformation. Their modeling studies suggested that this loop was in the binding site for PIP 2 and that this mode of binding correctly positioned the lipid for phosphoryl transfer from ATP.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several PI3K inhibitors are under development as possible cancer therapeutic agents . However, as different PI3K isoforms have different biological functions, an effective PI3K inhibitor has to be isoform‐selective to avoid side effects . Furthermore, depending on the activation mechanism of the associated oncogenic mutation, it may be necessary to design mutant‐specific inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Subclass IA kinases are heterodimers composed of two subunits, a catalytic p110 subunit and a regulatory p85 subunit. The three PI3K isoforms (PI3Kα, PI3Kβ, and PI3Kδ) contain different p110 sequences (p110α, p110β, and p110δ) (Gabelli et al 2010). …”
Section: Introductionmentioning
confidence: 99%